Development and Research on the Art Element Database Teaching Model in Higher Art Education - Zhu, Lingwei; Yongsorn, Chatupol; Areekul, Chananporn (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
Against the backdrop of the strategy of cultural confidence, the contemporary influence of traditional art and culture has been on the rise, forging a strong sense of cultural identity and consciousness of inheritance among young people in particular. Integrating it into modern art education has thus become a core research topic in the field of higher art education in China. Focusing on the improvement of higher art education quality and the pain points in art talent cultivation, this paper proposes an innovative integration path of “Traditional Art Element Database + ADDIE Teaching Method”, and constructs a student-centered (SC) Art Element Database Teaching Model with practical value, aiming to accurately empower students’ creative generation and creative skill enhancement. The research adopts the Delphi method to establish the framework of the teaching model, collects empirical data through multiple methods such as questionnaire surveys (targeting students majoring in higher art) and in-depth expert interviews (covering art education scholars and industry creators), and completes data verification and model effectiveness validation by means of SPSS statistical analysis and ANOVA (Analysis of Variance). The research results show that this teaching model not only exerts a significant positive impact on fostering the cultural literacy and innovative ability of students majoring in higher art, but also infuses cultural genes into China’s higher art education, promoting its transformation towards openness, innovation, and diversity. This study provides an operable practical paradigm for the educational inheritance of traditional art, as well as data support and theoretical reference for the teaching reform of higher art education.